Pressions et expressions de normes dans les pratiques d’enseignement de l’histoire au secondaire - Sabrina Moisan; Frédéric Saussez (Recherches en Éducation)
High school history teaching practices are recognized as having some common characteristics: predominance of lectures and a focus on historical contents rather than skills, for example. This article focuses on this observation and seeks to make sense of it by analyzing the specificities of the history teachers’ work. The question of the norm thus takes several figures in this research. In fact, observing practices allows disciplinary norms shaping the work of the history teacher to be considered, as well as the manner in which official prescriptions are received, integrated and transformed by history teachers, who thus create a more viable "action environment". The results show that this group of professionals has a specific disciplinary culture, which focuses on the organization and transmission of historical knowledge and the construction of what we call the "homemade learning book".